Effect of light elements on the sound velocities in solid iron: Implications for the composition of Earth's core - Badro, James; Fiquet, Guillaume; Guyot, François; Gregoryanz, Eugene; Occelli, Florent; Antonangeli, Daniele; d'Astuto, Matteo (Earth and planetary science letters, 2007)
We measured compressional sound velocities in light element alloys of iron (FeO, FeSi, FeS, and FeS2) at high-pressure by inelastic X-ray scattering. This dataset provides new mineralogical constraints on the composition of Earth's core, and completes the previous sets formed by the pressure–density systematics for these compounds. Based on the combination of these datasets and their comparison with radial seismic models, we propose an average composition model of the Earth's core. We show that the incorporation of small amounts of silicon or oxygen is compatible with geophysical observations and geochemical abundances. The effect of nickel on the calculated light element contents is shown to be negligible. The preferred core model derived from our measurements is an inner core which contains 2.3 wt.% silicon and traces of oxygen, and an outer core containing 2.8 wt.% silicon and around 5.3 wt.% oxygen.